1986
DOI: 10.1007/bf00687949
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus clearance in chronic inflammatory demyelination

Abstract: The distribution of canine distemper virus (CDV) antigen was examined in the brains of 14 dogs with chronic nervous distemper using a monoclonal antibody against a major viral protein. In ten of these dogs, neutralizing anti-CDV antibody titers were determined in serum and unconcentrated cerebrospinal fluid (CSF). In 19% of the inflammatory demyelinating lesions, large amounts of CDV antigen were found; in 34% of these lesions only residual traces of virus were seen and in almost half of the lesions (47%) no C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 15 publications
3
51
0
Order By: Relevance
“…In addition, viral antigen was not found in the CNS by either immunohistochemical or in situ hybridization techniques. 3,20 Louping ill infection is endemic in sheep in certain parts of Ireland, and dogs can be infected with this virus. 13,19 Histopathologic findings did not correlate with those previously reported in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, viral antigen was not found in the CNS by either immunohistochemical or in situ hybridization techniques. 3,20 Louping ill infection is endemic in sheep in certain parts of Ireland, and dogs can be infected with this virus. 13,19 Histopathologic findings did not correlate with those previously reported in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…TUNEL staining was markedly in the astrocytes with staining in only a number of inflammatory cells. These cells are related to virus elimination from CNS and can increase lesion severity and cellular cytotoxity against virus-infected cells (1,21). In also, the astrocytes are main target for CDV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CDV can persist in white matter areas outside the demyelinating lesions [10,158]. Persistence of CDV would, rather than being caused by a defect in the virus itself, mostly be related to restricted infection and non-cytolytic spread, as was also postulated, in a slightly different way, for the acute phase.…”
Section: Chronic Phasementioning
confidence: 91%